The Art of Logic in Muslim Scholarship: A Study of Mantiq Transmission and Reception in Indonesia - Fanani, Ahwan; Widigdo, Mohammad Syifa Amin (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
Although the Islamic art of logic (mantiq) has circulated for more than two centuries in Indonesia, the mantiq works and their functions obtain little academic attention. In this regard, the article aims to study how the mantiq works entered and spread in Indonesia and what functions they play in Islamic educational and scholarship settings. This writing employs a qualitative-historical approach by reading critically primary and secondary works of literature related to the study of logics in the Muslim world, especially in Indonesia, in order to analyze how those logical concepts and scholarship spread and are used in Islamic scholarly works in Indonesia. In the end, the article finds that the spread and development of mantiq works in Indonesia primarily stem from the international learning networks of Indonesian Muslim scholars (ʿulama’), centered in Mecca, Madina, and Cairo. The Indonesian ʿulama, who used to study in the Middle East, brought the mantiq to Indonesia. It is instrumental and required knowledge for understanding scientific and scholarly traditions in Islam, such as Islamic law (fiqh) and theology (kalam). Furthermore, mantiq plays a crucial role as an instrument for academic debates among scholars from different religious affiliations on whether religious or non-religious topics.